An experimental study to investigate the effects of venlafaxine and escitalopram on anticonvulsant activity of conventional antiepileptic drugs in mice - Singh, Santosh Kumar; Singh, Anamika (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Depression is a common psychiatric comorbidity in patients with epilepsy which remains often untreated, due to concern of antidepressant induced seizures. The safety status of selective serotonin reuptake inhibitors (SSRIs) in epileptics is controversial. Methods: Phase I acute effect of venlafaxine and escitalopram on the seizure threshold was studied. Phase II, the acute effects of test ADDs on the effective dose of AEDs viz valproate, phenobarbitone and phenytoin were studied in maximal electroshock (MES). Phase III- same study design as in phase II except that AEDs and ADDs were administered daily for 28 days. Results: Venlafaxine raised the electroconvulsive threshold in a dose dependant manner in phase I, however it was significant at a dose of 25mg/kg. In phase II, a significant reduction in ED50 of valproate was observed when it was co-administered with venlafaxine at dose of 12.5 and 25mg/kg, whereas ED50 of phenobarbitone was significantly reduced at a dose of 25mg/kg. Chronic administration of venlafaxine at 12.5mg/kg daily reduced ED50 of valproate. At 25mg/kg daily ED50 of all the three studied AEDs was reduced, Escitalopram 8mg/kg significantly raised the electroconvulsive threshold value in phase 1, Escitalopram administered in the dose of 8mg/kg reduced the ed50 value of valproate. Escitalopram given in dose of 4 and 8mg/kg reduced the ED50 value of valproate. Conclusions: From this finding, it may be concluded that venlafaxine and escitalopram administered either alone or in combination with AEDs acutely or chronically, exhibit anticonvulsant action.